Mitochondrial pyruvate import is a metabolic vulnerability in androgen receptor-driven prostate cancer. Issue 1 (January 2019) - Bader, David A.; M.Hartig, Sean; Putluri, Vasanta; Foley, Christopher; Hamilton, Mark P.; Smith, Eric A.
No abstract available